2011
DOI: 10.2139/ssrn.1861874
|View full text |Cite
|
Sign up to set email alerts
|

The Causal Relationship between Energy Use and Economic Growth in Switzerland

Abstract: This paper investigates the relationships between energy consumption and economic growth in Switzerland over the period 1950-2010. We apply bounds testing techniques to different energy types separately. Robustness tests are performed by including additional variables and restricting the analysis to the period after 1970. The results show that there exist robust long run relationships going from real GDP towards heating oil and electricity consumption. The relationship between heating oil and GDP is in fact bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 38 publications
(13 reference statements)
1
28
1
Order By: Relevance
“…In other words, policies in relation to energy conservation can be enacted without any effect on economic growth. This hypothesis is demonstrated by [26] …”
Section: Conservation Hypothesismentioning
confidence: 82%
“…In other words, policies in relation to energy conservation can be enacted without any effect on economic growth. This hypothesis is demonstrated by [26] …”
Section: Conservation Hypothesismentioning
confidence: 82%
“…Taking China as an example, Wang et al (2011) demonstrated the existence of short-run and long-run causality running from energy consumption to economic growth using a multivariate causality test. Similar studies were taken in Russia by Zhang (2011), in Switzerland by Baranzini et al (2013), and in Turkey by Yalta (2011). In addition, Burke et al (2015) explored the short-run effects of GDP growth on CO 2 emissions for 189 nations taking 1961-2010 into consideration.…”
Section: Introductionmentioning
confidence: 93%
“…Modern researchers place special emphasis on analyzing the inter-relation between the GDP and economic activity, eventually affecting the developments of energy intensity in an economy (Dergiades et al 2013;Fuinhas and Marques 2012;Yuan et al 2008;Baranzini et al 2013). It is noted that energy consumption in economically developed countries is much more resilient to drastic changes in the economic situation than in developing countries.…”
Section: Introductionmentioning
confidence: 99%